The Significance of Entrepreneurial Orientation on Firm Performance Through Innovation Capability - Pusparini, Helena I Gusti Ayu Putu; Indirawati, Donna Meilia; Adi, I Ketut Yudana; Azhari, Azhari (Universitas Pendidikan Nasional, 2024)
Companies must restructure the resources and capabilities to enhance performance. In a swiftly evolving competitive business environment, these resources and capabilities need to be effectively organized, integrated, and utilized. Consequently, companies should develop an entrepreneurial orientation as a strategy to guide entrepreneurial decisions and activities, focusing on how to leverage resources to convert innovation capabilities into performance. This research investigated the impact of entrepreneurial orientation on innovation capability and firm performance. This study focused on SMEs in Bali, Indonesia, with a sample size of 396. Data were gathered from managers of these SMEs, who served as the research respondents. An online questionnaire was administered through Google Forms and sent via email, resulting in 168 valid responses. Data analysis was performed using SEM PLS, with WarpsPLS 7.0 software. The results indicated a significant impact of entrepreneurial orientation on innovation capability and firm performance. Additionally, innovation capability positively and significantly influenced firm performance. The study also revealed that innovation capability mediates the relationship between entrepreneurial orientation and firm performance. When discussing innovation capabilities, refer to the routine actions involved in configuring capabilities and resources. Enhancing performance requires more than merely altering these capabilities and resources. Entrepreneurial orientation must play a crucial role in intensifying a company's innovation capabilities, which are essential for transforming into firm performance